2022
DOI: 10.1002/smi.3170
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the perceived stress scale (pss‐10) with breast cancer patients

Abstract: Breast cancer diagnosis is one of the most difficult events that a woman can experience during her life and it usually produces high levels of stress. Global measures of perceived stress are useful for screening and for comparing stress levels between cancer patients and other clinical and nonclinical populations. One such instrument that is widely used is the Perceived Stress Scale (pss-10), but its psychometric properties have scarcely been analysed with breast cancer patients.The aim of this study was to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 97 publications
4
15
0
Order By: Relevance
“…McDonald's omega and Cronbach's alpha coefficients in the present sample were 0.90 for depression, 0.84 for anxiety, 0.90 for stress, and 0.95 for total scores. Perceived helplessness subscale of the 10-item version of the Perceived Stress Scale (PSS-10; Cohen et al, 1983;Cohen and Williamson, 1988), in its Spanish version (Remor, 2006) that has been validated in Spanish breast cancer patients (Soria-Reyes et al, 2023). This subscale comprises six items (e.g., "In the last month, how often have you felt nervous and stressed?…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…McDonald's omega and Cronbach's alpha coefficients in the present sample were 0.90 for depression, 0.84 for anxiety, 0.90 for stress, and 0.95 for total scores. Perceived helplessness subscale of the 10-item version of the Perceived Stress Scale (PSS-10; Cohen et al, 1983;Cohen and Williamson, 1988), in its Spanish version (Remor, 2006) that has been validated in Spanish breast cancer patients (Soria-Reyes et al, 2023). This subscale comprises six items (e.g., "In the last month, how often have you felt nervous and stressed?…”
Section: Instrumentsmentioning
confidence: 99%
“…Another widely used instrument that includes a stress subscale is the Depression, Anxiety, and Stress Scales (DASS-21; Lovibond and Lovibond, 1995 ), whose psychometric properties have also been examined in general populations ( Lee et al, 2019 ; Zanon et al, 2020 ) and in specific populations such as adolescents ( Moore et al, 2016 ; Shaw et al, 2017 ), Chinese hospital workers ( Jiang et al, 2020 ), the Korean working population ( Jun et al, 2018 ), menopausal Arab women ( Bener et al, 2016 ), and psychiatric patients ( Ali et al, 2021 ). Both these scales are global measures of perceived stress that have also been used in people with cancer ( Golden-Kreutz et al, 2004 ; Bener et al, 2016 ; Fox et al, 2018 ; Kumar et al, 2019 ; Cerezo et al, 2022 ; Soria-Reyes et al, 2023 ). However, for individuals who are facing particularly overwhelming experiences, such as a diagnosis of breast cancer, global measures of this kind should be complemented by other more specific ones.…”
Section: Introductionmentioning
confidence: 99%
“…Using a global measure of perceived stress is useful for screening purposes and for comparing stress levels between infective endocarditis patients and other clinical and nonclinical populations. The PSS-10 has become one of the most widely used instruments for measuring perceived stress [ 31 ], with both empirical studies and systematic reviews showing it to have strong psychometric properties in numerous clinical and nonclinical samples [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 10-item Perceived Stress Scale (PSS) ( Cohen, 1988 ) was collected at each trimester study visit via interviewer-administered questionnaire in either Spanish or English. The 10 item PSS scale has been validated and utilized in countless studies worldwide to assess perceived stress ( Andreou et al, 2011 ; Anwer et al, 2020 ; Bastianon et al, 2020 ; Dao-Tran et al, 2017 ; Ezzati et al, 2014 ; González-Ramírez et al, 2013 ; Huang et al, 2020 ; Makhubela, 2020 ; Manzar et al, 2019 ; Mondo et al, 2021 ; Reis et al, 2019 ; Roberti et al, 2006 ; Ruisoto et al, 2020 ; Smith et al, 2014 ; Soria-Reyes et al, 2022 ), has been shown to be superior in psychometric properties compared to the 4-item or 14-item PSS scale ( Lee, 2012 ), and has been validated for use within Hispanic populations ( Baik et al, 2019 ). The scale measures the amount of perceived stress experienced by the participant with questions to capture how uncontrollable, unpredictable, and over-loading one’s life was within the last month (30 days).…”
Section: Methodsmentioning
confidence: 99%